Acquisition of Publications through NTIS - Is it Economical? - Ragavan, M. C. (Journal of Information and Knowledge, 1982)
The National Technical Information Service of D .S. Department of Commerce is the central source for the public sale of government sponsored research, development and engineering reports and other agencies. It is also a central source for the federally generated machine processable data files and related software. The NTIS has appointed agents in India for processing orders emanating from within the country. The paper highlights the experiences in collection development through the experience in collection development through the NTIS service and raises the basic question whether we are paying the right price for the documents acquired Case studies are cited.